2019
DOI: 10.1002/jcla.23102
|View full text |Cite
|
Sign up to set email alerts
|

The RAS‐PI3K‐AKT‐NF‐κB pathway transcriptionally regulates the expression of BCL2 family and IAP family genes and inhibits apoptosis in fibrous epulis

Abstract: Background Epulis has a tumor‐like appearance but is considered to be a massive reactive lesion rather than a true neoplasia. Limited information about the pathogenesis of epulis is available. The purpose of our study was to identify potential signaling pathways in fibrous epulis through transcriptome profiling. Methods Differentially expressed genes (DEGs) between fibrous epulis lesions and normal gingival tissues were detected using RNA sequencing (RNAseq). The expression levels of eighteen genes were valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The PI3K signalling pathway plays an important role after the overexpression of BCL2. PI3K/AKT/BCL2 is a common apoptotic inhibitory approach in other previous studies 41‐43 . Activated AKT directly promotes the expression of BCL2 to play an anti‐apoptotic role 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K signalling pathway plays an important role after the overexpression of BCL2. PI3K/AKT/BCL2 is a common apoptotic inhibitory approach in other previous studies 41‐43 . Activated AKT directly promotes the expression of BCL2 to play an anti‐apoptotic role 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, increasing resistance to tumor cell death by immune cells also could induce immune evasion including increased expression of cellular FLICE-like inhibitory protein (cFLIP) or inhibitor of apoptosis proteins (IAPs). NF-κB pathway could positively regulate expression of IAP family, leading to the proliferation and apoptosis inhibition 50 , while up-regulation of RNA demethylase ALKBH5 could improve the activation of the NF-κB pathway in carcinogesis 51 . The RNA demethylase ALKBH5 could increase the IAPs expression by activating the NF-κB signals in tumor cells to resist the immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…COL6A6 has been reported to be down-regulated in breast cancer [27][28][29] . Significant down-regulation of COL6A5 has been proved in esophageal squamous cell carcinoma 30 and fibrous epulis 31 . Wang and the colleagues has found that collagen type VI may interacts with ROBO2 in esophageal squamous cell carcinoma development, and ROBO2 serves as a tumor suppressor during malignant process 32 .…”
Section: Discussionmentioning
confidence: 99%